The Impact of a Reading Room's Closure on Collection Development. - Heather Lewin (Issues in Science and Technology Librarianship)
This paper discusses the preparations for the closure of Iowa State University's Physical Science Reading Room from the perspective of collection management and development. The anticipated changes to the reading room collection provided an opportunity to analyze the core physical sciences collection in regards to composition, space occupied, and use. Additionally, this paper reviews the data gathered to determine the effects of material accessibility and use on future collection development decisions. Reprinted by permission of the publisher.